2010
DOI: 10.3390/molecules15118048
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Effect of 1’S-1’-Acetoxychavicol Acetate from Alpinia Conchigera on Human Cancer Cells

Abstract: 1’-(S)-1’-Acetoxychavicol acetate (ACA) isolated from the Malaysian ethno-medicinal plant Alpinia conchigera Griff. was investigated for its potential as an anticancer drug. In this communication, we describe the cytotoxic and apoptotic properties of ACA on five human tumour cell lines. Data from MTT cell viability assays indicated that ACA induced both time- and dose-dependent cytotoxicity on all tumour cell lines tested and had no adverse cytotoxic effects on normal cells. Total mortality of the entire tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
0
41
0
1
Order By: Relevance
“…The 1′S-1′-acetoxychavicol acetate (ACA) is a natural compound isolated from the wild ginger, Alpinia conchigera . We have previously reported that it is able to induce cytotoxicity when used as stand-alone and potentiates the effects of cisplatin when used in combination on different cancer cells including cervical cancer 6,7…”
Section: Introductionmentioning
confidence: 99%
“…The 1′S-1′-acetoxychavicol acetate (ACA) is a natural compound isolated from the wild ginger, Alpinia conchigera . We have previously reported that it is able to induce cytotoxicity when used as stand-alone and potentiates the effects of cisplatin when used in combination on different cancer cells including cervical cancer 6,7…”
Section: Introductionmentioning
confidence: 99%
“…The use of 1’S-1’-acetoxychavicol acetate (ACA), which is a phenylpropanoid naturally found within various Zingiberaceae family members, has been traditionally associated with a number of various medicinal properties including anti-ulceration [15], anti-allergic [16], anti-inflammatory and anti-cancer activities [17,18]. Previous studies have shown ACA to be associated with the production of intracellular reactive oxygen species (ROS) [19], inhibition of xanthane oxidase (XO) activity [20], inhibition of nitric oxide synthase (NOS) expression [21], inhibition of polyamine synthesis [22], induction of apoptosis via mitochondrial/Fas-mediated dual mechanism [19] and as a potential NF-κB inhibitor [23-25].…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan data yang diperoleh, didapati bahawa mod kematian secara apoptosis merupakan mod kematian utama bagi sel hepar Chang setelah dirawat dengan esktrak heksana A. conchigera (Rajah 2). Hasil kajian ini adalah selari dengan kajian yang dilakukan oleh Khalijah et al (2010) iaitu kematian sel yang disebabkan oleh 1'-S-1'-Acetoxychavicol Acetate daripada ekstrak A. conchigera adalah secara apoptosis. Selain itu, kajian ini turut selari dengan kajian oleh In et al (2011), metabolit tunggal iaitu AEA yang diasingkan daripada ekstrak rizom A. conchigera telah menyebabkan kematian sel adenokarsinoma payudara (MCF-7) secara apoptosis.…”
Section: Hasil Dan Perbincanganunclassified